Insights into the role of in-situ and ex-situ hydrogen peroxide for enhanced ferrate(VI) towards oxidation of organic contaminants - Mengfan Luo; Hongyu Zhou; Peng Zhou; Leiduo Lai; Liu, Wen; Zhimin Ao; Gang Yao; Heng Zhang; Bo Lai (Water Research, 2021)
Recently, several studies have been conscious of the promotion effect of hydrogen peroxide (H2O2), a self-decay product of ferrate (Fe(VI)), on Fe(VI) to oxidize contaminations, but the pivotal activation mechanism has not been thoroughly evaluated. This work aims to compare and reveal the promoting mechanism of H2O2 in Fe(VI) and Fe(VI)−H2O2 processes, and to illustrate the practical use potential of Fe(VI)−H2O2 system. Many lines of evidence verified the involvement of •OH and O2•− in pollutant degradation were excluded in Fe(VI) and Fe(VI)−H2O2 systems, meaning that high dosage of H2O2 cannot trigger an activation pathway different from in-situ H2O2. The better oxidation performance of the Fe(VI)−H2O2 system than Fe(VI) alone was ascribed to the catalytic role of in-situ and ex-situ H2O2, which can directly and/ or indirectly facilitate the formation of Fe(IV) and Fe(V). Considering the structural similarity of peroxymonosulfate (PMS) and peroxydisulfate (PDS) with H2O2 as well as their universality in water pollutant remediation, the oxidation properties and reactive oxidants of Fe(VI)−PMS and Fe(VI)−PDS processes were also examined. Besides, the Fe(VI)−H2O2 system suffered from less restriction by inorganic ions and natural organic matter, and exhibited satisfactory pollutant removal effects in real water. Overall, this work provides a further and comprehensive cognition about the role of H2O2 in Fe(VI) and Fe(VI)−H2O2 systems.
Keywords: Ferrate(VI); hydrogen peroxide; Self-decay; Sulfamethoxazole; Two-electron transfer